1999
DOI: 10.1107/s090744499900801x
|View full text |Cite
|
Sign up to set email alerts
|

How RhoGDI binds Rho

Abstract: Like all Rho (Ras homology) GTPases, RhoA functions as a molecular switch in cell signaling, alternating between GTP- and GDP-bound states, with its biologically inactive GDP-bound form maintained as a cytosolic complex with RhoGDI (guanine nucleotide-exchange inhibitor). The crystal structures of RhoA-GDP and of the C-terminal immunoglobulin-like domain of RhoGDI (residues 67-203) are known, but the mechanism by which the two proteins interact is not known. The functional human RhoA-RhoGDI complex has been ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 38 publications
3
61
0
Order By: Relevance
“…We confirmed this finding directly, by the binding of recombinant ADP-ribosylated RhoA to recombinant GDI-1 thereby excluding the involvement of any additional factors. From the structure of the RhoA-GDI-1 complex can be deduced that the ADP-ribose at Asn-41 is directed to the solvent and may not hamper the formation of the complex (46). ADP-ribosylation, however, changes the binding properties of Rho to GDI-1.…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed this finding directly, by the binding of recombinant ADP-ribosylated RhoA to recombinant GDI-1 thereby excluding the involvement of any additional factors. From the structure of the RhoA-GDI-1 complex can be deduced that the ADP-ribose at Asn-41 is directed to the solvent and may not hamper the formation of the complex (46). ADP-ribosylation, however, changes the binding properties of Rho to GDI-1.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the SH3-SH2-SH3 domains of Vav (i.e., Vav-C) may recruit Rac.GDP indirectly, perhaps via DOCK180 or another protein interaction. Several groups have shown that the inactive form of Rac exists in a cytosolic complex with RhoGDI and that GEFs are unable to promote nucleotide exchange while Rac is in this complex (Hancock and Hall, 1993;Longenecker et al, 1999). Whether RhoGDI remains bound, or is induced to dissociate, for example, by the interaction with ezrin/radixin/ moesin family proteins (Takahashi et al, 1997), which are found at phagosomes (Defacque et al, 2000), is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although some sample-to-sample variability in the amounts of peptides eluting at each point was seen, substantial dimer peaks were observed only in oxidized samples, and aggregates eluting at 9.0 ml were seen only in fresh, nonoxidized samples. mAU, milli-absorbance units exposed residues of RhoA (11,17,19,23,25,28) had little effect on the ability of the peptide to inhibit RSV (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%